Perancangan Aplikasi Alat Uji Motor Listrik UAV Berbasis Graphic User Interface (GUI) Menggunakan Software Python - Aisyah, Luthfa Refihat; Azka, Muizuddin; Musthofa, Ahmad; Yulianto, Katri (Jurnal Sains dan Teknologi Penerbangan, 2024)
The development and test of electric motors on Unmanned Aerial Vehicles (UAV) requires a sophisticated and efficient approach. This research discusses the design of innovative UAV electric motor test equipment applications using Python software-based Graphic User Interface (GUI). The main objective of this application is to provide an intuitive and effective user interface to control, monitor, and test the performance of UAV electric motors. In this study, the waterfall method was used for system development. Preliminary test results show that the application is easy to use and efficient in testing UAV electric motors. It is hoped that this design will help the development of UAV technology by providing easy-to-use and reliable test equipment for researchers, technicians, and developers in the field of unmanned flight.